High risk factors, molecular features and clinical management for radioactive iodine-refractory differentiated thyroid carcinoma - Ma, Tengyun; Xie, Yiting; Long, Xinyi; Ye, Feng (Frontiers in Oncology, 2025)
Despite the generally favorable prognosis of differentiated thyroid carcinoma (DTC) following surgery and radioactive iodine (RAI) therapy, approximately 10% of cases eventually develop resistance to RAI. This condition, known as radioiodine-refractory differentiated thyroid carcinoma (RAIR-DTC), is associated with a poor prognosis, with a 10-year survival rate of only 10% from the time of metastasis detection. The limited availability of safe and effective alternative treatments poses a significant challenge to clinical management. However, early identification and intervention targeting high-risk factors are critical for preventing disease progression. Integrating current insights into DTC pathogenesis with established clinical strategies offers valuable opportunities to inform the development of novel therapies and improve patient outcomes. Hence, in this review, we first examine high-risk predictors of RAIR, including demographic factors (e.g., age, sex), gene mutations (e.g., RAS, BRAF, TERT), high-risk histopathological subtypes (e.g., extrathyroidal extension and the tall cell variant), and serum biomarkers (e.g., thyroglobulin and Cyfra 21.1), all of which are widely recognized for monitoring and risk stratification. Notably, we also emphasize that inappropriate pharmacological management of comorbidities—such as diabetes, myeloid leukemia, and hypertension—may suppress sodium-iodide symporter (NIS) expression and RAI uptake, thereby contributing to RAIR development. We then summarize the molecular mechanisms underlying impaired NIS expression and function in RAIR-DTC, followed by a discussion of recent advances in clinical treatment, focusing on the efficacy and safety of both approved and investigational therapeutic agents.